'Ideal Home' Assertion of Istanbul. (2016) - Engincan, Pinar
Abstract: As from 1980's and especially for the last decade, Istanbul seems to be a huge construction site, which is not a coincidence when all the policies related to construction such as housing, urbanization, urban transformation, marketing policies and stimulation of citizens' evolution to a consumption society are taken into consideration. In this period – from 1980's till today – a wide range of products belong to the "Ideal Home" assertion was built almost everywhere of the city. Nowadays with an increasing numbers of houses as 'strolling instruments' are for sale; but how about "home" itself? As is known, "someone's home" is not just a location and a structure with natural or/and built environment of a neighbourhood, but it is a "place" socially, psychologically and emotionally meaningful to its user/owner. At this point, it becomes reasonable to examine the relation between the "ideal home" produced and the "ideal home user/owner" in the context of appropriation, attachment and identity as home making mechanisms. The theoretical background of the research depends on the literature of architecture and urban design particularly in the field of environmental psychology that is focused on the interaction between place and human. These related literatures are re-examined in order to designate the specific behavioural components of home making. According to these components identified a case study is carried out in the residential areas produced with an assertion of ideal home in Istanbul. In-depth semi-structured interviews searching for behavioural components of home making were conducted on thirty families from six different locations in the city. Findings indicate that behavioural adaptation differs in a variety of features of the houses such as; local characteristics of the urban areas the houses are built in, existing housing design, target group of houses, relations with other users etc. Additionally, it seems that housing modifications commonly provided a more supportive environment in a great deal of houses but on the contrary, modifications are disproving the "ideal home" assertion and in some families have adverse effects.